Analisis Kebijakan Hukum Pemerintah Indonesia terhadap Tenaga Kerja dalam Konteks Free Flow of Services dan Skilled Labour dalam Kerangka ASEAN Economic Blueprint - Arinda Milahayu Indraswari Anny (International Forum of Researchers and Lecturers, 2025)
The Bali Concord II Declaration became the basis for the establishment of the ASEAN Economic Community (AEC) which aims to create a single market with five freedoms, including skilled labor mobility. However, Indonesia faces challenges in improving the quality of its human resources to compete in the regional market. Indonesia-Germany cooperation, in terms of vocational education development in Indonesia, offers a strategic opportunity to produce competent graduates according to international standards. Policy support such as Presidential Regulation No. 68 of 2022 on the revitalization of vocational education strengthens this effort, enabling technology transfer, strengthening industry-based curriculum, and improving the quality of teaching staff. Effective implementation is expected to make Indonesia one of the leading countries in skilled labor exports in ASEAN, while strengthening national economic competitiveness in the era of regional integration.